2018
DOI: 10.1007/s12088-018-0760-y
|View full text |Cite
|
Sign up to set email alerts
|

Fish Gut Microbiome: Current Approaches and Future Perspectives

Abstract: In recent years, investigations of microbial flora associated with fish gut have deepened our knowledge of the complex interactions occurring between microbes and host fish. The gut microbiome not only reinforces the digestive and immune systems in fish but is itself shaped by several host-associated factors. Unfortunately, in the past, majority of studies have focused upon the structure of fish gut microbiome providing little knowledge of effects of these factors distinctively and the immense functional poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(110 citation statements)
references
References 132 publications
5
83
2
2
Order By: Relevance
“…Despite this known biological importance, the composition of the intestinal microbiome in wild fish populations remains poorly understood. To date, studies of the fish intestinal microbiome have revealed a limited phylogenetic diversity, with genera from Proteobacteria, Firmicutes, and Bacteroidetes constituting up to 90% of the sequence reads across different species (Verner-Jeffreys et al, 2003;Ward et al, 2009;Ghanbari et al, 2015;Givens et al, 2015;Riiser et al, 2018;Talwar et al, 2018). Apart from this relatively low bacterial diversity, several studies have reported a limited geographical differentiation between intestinal bacterial communities, indicating a strong influence of host-associated factors on the composition of the gut microbiome (Ye et al, 2014;Llewellyn et al, 2016;Riiser et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this known biological importance, the composition of the intestinal microbiome in wild fish populations remains poorly understood. To date, studies of the fish intestinal microbiome have revealed a limited phylogenetic diversity, with genera from Proteobacteria, Firmicutes, and Bacteroidetes constituting up to 90% of the sequence reads across different species (Verner-Jeffreys et al, 2003;Ward et al, 2009;Ghanbari et al, 2015;Givens et al, 2015;Riiser et al, 2018;Talwar et al, 2018). Apart from this relatively low bacterial diversity, several studies have reported a limited geographical differentiation between intestinal bacterial communities, indicating a strong influence of host-associated factors on the composition of the gut microbiome (Ye et al, 2014;Llewellyn et al, 2016;Riiser et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…), and the emerging importance of understanding the functional profiles of gut microbial communities through metagenomic analyses (Talwar et al. ). This review seeks to briefly touch on overarching themes of fish gut microbiome research, while highlighting numerous potential real‐world applications of fish gut microbiome research across sub‐disciplines in the aquatics and fisheries fields.…”
Section: The Gut Microbiotamentioning
confidence: 99%
“…The gill microbiome, and the interaction with N. perurans, may thus shape the host's immunological machinery and response to infection [12]. As in the case of other sh pathologies associated with microbiomes [35], AGD is thus a multifactorial gill disease [4], requiring complex interactions between environmental factors (temperature, salinity, etc. ), the sh microbiome, the host's metabolism, and pathogens.…”
Section: Freshwater Bathing Appears To Regulate Response Of N Peruramentioning
confidence: 99%